Changes in quality of life scores with intravenous immunoglobulin or plasmapheresis in patients with myasthenia gravis. Issue 1 (15th November 2012) - Barnett, Carolina; Wilson, Graham; Barth, David; Katzberg, Hans D; Bril, Vera
Abstract : Background: Intravenous immunoglobulin (IVIG) and plasmapheresis (plasma exchange (PLEX)) have comparable efficacy in reducing the Quantitative Myasthenia Gravis Score for disease severity (QMGS) in patients with moderate to severe myasthenia gravis (MG). Objective: To determine if the improvement in the quality of life (QOL) after immunomodulation is comparable with either IVIG or PLEX. Methods: 62 patients participated in the MG-QOL-60 study, completing the questionnaire at baseline and at day 14 after treatment. The MG-QOL-15 scores were computed from the MG-QOL-60 questionnaire responses. We analysed the change in the QOL scores from baseline to day 14 in both treatment groups. Results: The scores in both QOL scales decreased at day 14 in the IVIG and PLEX groups, without significant difference between groups (QOL-15: IVIG −5.7±8.5, PLEX: −7.0±7.6, p=0.52; QOL-60: IVIG −13.3±16.9, PLEX −18.5±22.0, p=0.41). The improvement in QOL showed a good correlation with the decrease in QMGS. There was an excellent correlation between the MG-QOL-15 and MG-QOL-60 scores at baseline and at day 14. Conclusions: This study of MG-QOL changes supports recent findings that IVIG and PLEX are comparable in the treatment of patients with moderate to severe MG and worsening symptoms. Furthermore, our study supports the use of the MG-QOL-15 as a secondary outcome measure in future clinical trials in MG.